Vitamin D Status and Associated Factors in Neonates in a Resource Constrained Setting. (5th July 2018) - Bhimji, Khadija Murtaza; Naburi, Helga; Aboud, Said; Manji, Karim
Abstract : Vitamin D deficiency (VDD) is emerging as a serious public health problem globally; however due to lack of resources, vitamin D levels are not routinely measured among neonates. The study was conducted to determine vitamin D levels in neonates and factors associated with the same. A cross-sectional study was conducted among neonates admitted at neonatal ward of a tertiary care hospital. Means and proportions were calculated from summarized data in frequency tables. Chi square test was used to determine association between vitamin D and various associated factors such as sex, infant birth weight, gestation age, parity of the mother, maternal age, and HIV status of the mother. A total of 170 neonates were studied, out of which 80% had vitamin D deficiency. Neonates born to HIV-infected mothers were significantly less likely to have vitamin D deficiency (OR 0.21, 95% CI 0.06 – 0.77, p = 0.009). Subgroup analysis revealed the association to be stronger in terms neonates (p = 0.005). The association was not observed among preterm newborns. The prevalence of vitamin D deficiency in neonates was observed to be very high and needs more attention.